2017
DOI: 10.1016/j.bbi.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of IL-1β-induced reduction of human neurogenesis by omega-3 fatty acids and antidepressants

Abstract: HighlightsInflammation and reduced neurogenesis are associated with the pathophysiology of depression.IL-1β decreased neurogenesis in human hippocampal progenitor cells.EPA, DHA, sertraline and venlafaxine prevented the IL-1β-induced reduction in neurogenesis.EPA and DHA reversed the IL-1β-induced increase in kynurenine levels.EPA, DHA, sertraline and venlafaxine decreased the upregulation of IDO and KMO mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 78 publications
6
105
1
1
Order By: Relevance
“…Monoaminergic antidepressants and also omega-3 fatty acids were demonstrated to reduce neurotoxic effects related to Trp breakdown (246). Omega-3 fatty acids contribute to the beneficial effects of the Mediterranean diet, which is regarded as anti-inflammatory diet (247).…”
Section: Nutrition Microbiome and Physical Activity And Its Associamentioning
confidence: 99%
“…Monoaminergic antidepressants and also omega-3 fatty acids were demonstrated to reduce neurotoxic effects related to Trp breakdown (246). Omega-3 fatty acids contribute to the beneficial effects of the Mediterranean diet, which is regarded as anti-inflammatory diet (247).…”
Section: Nutrition Microbiome and Physical Activity And Its Associamentioning
confidence: 99%
“…The effects of DHA on different brain cell populations has been most extensively studied in the rat hippocampus. Several studies have investigated the effects of DHA on hippocampal progenitor populations and hippocampal function and found that it promotes neuronal differentiation and survival through a number of mechanisms including increasing retinoid-X receptor and pro-neuronal bHLH gene expression (Calderon and Kim, 2007;Katakura, et al, 2009;Kim et al 2000;Dyall et al, 2010), it promotes progenitor proliferation in disease models (da Costa, et al, 2010;Borsini et al, 2017;Fiol-deRoque, et al, 2013), and it has a functional impact on learning and memory (Lozada et al, 2017;He et al, 2009). Our observations of SVZ cells have found the effects of DHA treatment on progenitor populations may differ significantly from the SGZ, such as a lack of a direct effect on the proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Besides IL-1 β , other inflammatory markers have also been noted to be involved in the pathogenesis of depression such as tumor necrosis factor- α (TNF- α ) and interferon- γ (IFN- γ ) [52]. Fish oils are relevant to this discussion because one study demonstrated that EPA and DHA, along with sertraline (SSRI) and venlafaxine (SNRI), were able to reverse the effects of IL-1 β at human hippocampal cells in vitro [4]. Similar findings have also been shown in clinical trials using patients treated with IFN- α to combat hepatitis C infections.…”
Section: Mechanism Of Actionmentioning
confidence: 99%